Performance and physiological effects of different descending strategies for cross-country mountain bike performance - Miller, M.; Macdermid, P.; Fink, P.; Stannard, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Physiological variables measured during cross-country mountain bike racing remain steady despite highly intermittent propulsive work demanded by variable terrain (Macdermid and Stannard, 2012), which may be due to musculo-tendonous damping of vibrations that are translated from the riding surface (Macdermid et al., 2014). Reports that descending performance is independent of mechanical propulsive work (Hurst and Atkins, 2006) suggest it may be possible to reduce pedaling on descents and better recover for subsequent ascents. This study investigated the vibrations, metabolic benefits and performance-related feasibility of eliminating pedaling while descending and compared these values to those measured on a road surface. Methods: Eight nationally competitive mountain bikers took part in this study. 24 hours after a laboratory fitness test, participants completed a field trial consisting of three descending conditions (off-road pedaling (DHP); off-road coasting (DHC), both 1.01 km, -16.3%; road (DHR), 1.03 km, -15.7%). After familiarization with the track used and practicing the coasting strategy, participants cycled uphill at race pace before randomly commencing DHC or DHP. DHR was completed at the mean velocity of the off-road trials. Power, heart rate, VO2, and tri-axial accelerations were recorded. Results: VO2 was significantly increased during DHP when compared with DHC (35.2 ± 4.8 vs 31.7 ± 3.9 ml/min/kg, respectively) despite no difference in vibrations and relatively low average power output (18.8 ±11.6 W). Pedaling did not elicit a performance benefit (DHC=142.5 ±29.2, DHP=139.9 ± 29.2 s) on the descent used in this study. Lower heart rate and oxygen uptake were observed in DHR versus both off-road trials, likely caused by the decrease in vibrations. Discussion: Despite relatively low power output, metabolic demand is exacerbated when pedaling on off-road descents compared with coasting. Elimination of propulsive work does not change vibration exposure but decreases oxygen cost, and importantly has no negative effect on performance. Vibrations experienced during road descending are relatively low, and accompany further reduce physiological demand. It is recommended that athletes focus on skills to increase descending speed without the addition of pedaling, and that equipment be used to decrease vibrations nearer to those seen on the road.